Estimation of serum potassium levels as a prognostic marker in acute organophosphorus poisoning in a tertiary care center - Parate, Tilottama R.; Bhure, Nitin H.; Parate, Ramesh U. (International Journal of Research in Medical Sciences, 2025)
Background: Organophosphorus compound poisoning is primarily a problem of the developing countries. Its widespread use and easy availability have increased the likelihood of poisoning with these compounds. Serum cholinesterase levels are easier to estimate and usually depressed after OP poisoning. Peradeniya OP poisoning scale has not been studied much in Indian scenario. Hypokalaemia is one of the most common electrolyte abnormalities associated with organophosphorus poisoning It could be a simple and effective system to determine the need for ventilatory support early on in the course. The data are scarce especially in central India regarding the OP poisoning and the consequent role of serum potassium in assessing the severity. Hence this study was undertaken to assess the severity of organophosphorus compound poisoning clinically by estimating serum potassium levels. Methods: A prospective study was performed among 100 cases of OP poisoning, from September 2022 to September 2024. On patient’s fulfilling inclusion criteria were investigated with serum Potassium at the time of admission and estimation of serum acetylcholinesterase were done on the day of admission. Results: Serum potassium levels were significantly low in subjects who required mechanical ventilation compared to those with normal potassium levels serum potassium levels and Potassium levels were significantly low in patients who developed respiratory failure and thus strongly correlated with clinical severity. Conclusions: Serum potassium levels show a strong degree of positive correlation with the severity of poisoning and can be used as a predictor of outcome in organophosphorus poisoning.